Urban community response supported by government: The case of COVID-19 management in Dhaka - Ahmed, Shamael; Rabbani, Mehnaz (Taylor and Francis, 2024)
This book chapter was published in the book named Regional Studies Policy Impact Books and the definite version is available at : https://www.tandfonline.com/eprint/YQJNIRBMJ4JTBDAQBEQF/full?target=10.1080/2578711X.2023.2196214